Pengaruh Core Stability Exercise Dan Ankle Balance Strategy Exercise Terhadap Keseimbangan Statis - Ramadhan, Syahrul; , Wahyuni SST.FT, M.Kes (2016)
Background: The balance is defined as the relative ability to control the body's center of mass (center of mass) or the center of gravity (center of gravity) to the plane fulcrum (the base of support). Interest body maintain balance is to support the body against gravity and other external factors, to maintain the body's center of mass to be aligned and balanced with a pivot field, and stabilize parts of the body when the other body parts move (Irfan, 2010). The balance involving a wide range of motion in each body segment, supported by the musculoskeletal system and the pivot field. The ability to balance the body mass with the abutting field will make people able to move effectively and efficiently. Objective: To determine whether there is influence core stability exercise against static equilibrium. To determine whether there is influence Ankle balance exercise against static equilibrium. To find out if there are differences in the provision of core stability exercise and balance exercise Ankle against static equilibrium Results: The results showed data on both groups 15-16 years of age, sex, male and female. The test results stated static balance data using functional reach test p = 0.005 group 1 and group 2 p = 0.004. Based on the test mann-withneyy two variables in both groups, testing of hypotheses using the data-gap treatment showed p = 0.020. Conclusions: Exercise core stability exercise can give the effect of an increase in static equilibrium in the first grade students of SMK N 1 Geneng. Ankle balance exercise strategy gives the effect of increasing the static equilibrium on the students of class 1 SMK N 1 Geneng. According to the research that has been done that ankle balance exercise is an exercise strategy that is giving the effect of increasing a better balance.